Synchronous papillary and medullary thyroid carcinoma: about a case - Yan-Quiroz, Edgar Fermín (2024)
The synchronous existence of papillary and medullary carcinoma is infrequent, and they can have a discrete or mixed presentation. About its pathogenesis, it is not entirely clear, however, various theories have currently been proposed where genetic mutations and local and environmental factors involved in its appearance are involved. According to their histological characteristics, these are highly variable, presenting different structural patterns. The therapeutic approach differs in both histopathological types, so it is important to know about the synchronous existence of these tumors.